Achieving sustainable cultivation of cassava Volume 1: Cultivation techniques - Clair, Hershey (2017)
Originating in South America, cassava is now grown in over 100 countries around the world. It is the third most important source of calories in the tropics after rice and maize. Its caloric value, as well as its ability to tolerate dry conditions and poor soils, makes it a key food security crop in developing countries, particularly in Africa. As demand for food grows, there is an urgent need to increase yields in the face of such challenges as climate change, threats from pests and diseases and the need to make cultivation more resource-efficient and sustainable.